DAMPAK PERUBAHAN PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) MENJADI 8 DIMENSI PROFIL LULUSAN PADA GURU DI SEKOLAH DASAR - Anisa Adha; Sri Marmoah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The graduate profile dimensions are an integral component that every student must possess after completing a learning and education process. The eight graduate profiles emphasize not only cognitive aspects but also the development of character and skills that students will need in their daily lives. The implementation of the change from the P5 program to the 8 graduate profile dimensions has not been fully implemented in various schools. The purpose of this study was to describe the impact of the change from P5 to the 8 Graduate Profile Dimensions on elementary school teachers. A qualitative method was used with a case study design aimed at understanding social phenomena descriptively. Data collection was carried out through literature review and interviews with teachers at SD N 1 Sindon. The results of the study explain that the change from P5 to the 8-dimensional graduate profile has an impact on several aspects, such as the implementation process, the level of teacher understanding, and implementation constraints, thus requiring new strategies in the implementation process of the 8-dimensional graduate profile program. Therefore, continuous evaluation and system strengthening are needed so that the objectives of the 8-dimensional graduate profile program can be better achieved optimally at the education level in Indonesia